ZnO-adipic acid composites as phase change material for latent heat thermal energy storage systems - N. R. Snekha; V. Hari Suthan; K. S. Suganthi; S. Naren Raggavendra; S. Sudharsan; R. Aishwarya; K. S. Rajan (Micro and Nano Systems Letters)
Abstract This work evaluates the use of zinc oxide nanorods as intensifiers of a latent heat thermal energy storage system working with adipic acid as the phase change material (PCM). By virtue of not participating directly in the solid–liquid and liquid–solid phase transition, ZnO-adipic acid composites (ZnO-adipic acid) possessed lower specific heat and latent heat. Our results have shown that the overall heat transfer coefficient during the freezing of PCM through heat transfer to a well-mixed liquid bath is amplified by 61%, when adipic acid is replaced with 2 wt.% ZnO-adipic acid. Heterogenous nucleation due to well-dispersed, ZnO nanorods caused this enhancement. The large enhancement in discharge rate of 2 wt.% ZnO-adipic acid during freezing overweighs higher degree of latent heat loss due to its repeated thermal cycling. The enhancement in overall heat transfer coefficient reported here (61%) is the highest reported so far for any latent heat thermal energy system employing adipic acid or its composites.